Impact of oral vancomycin on gut microbiota, bile acid metabolism, and insulin sensitivity - Vrieze, Anne; Out, Carolien; Fuentes, Susana; Jonker, Lisanne; Reuling, Isaie; Kootte, Ruud S.; van Nood, Els; Holleman, Frits; Knaapen, Max; Romijn, Johannes A.; Soeters, Maarten R.; Blaak, Ellen E.; et al. (Journal of hepatology, 2014)
Obesity has been associated with changes in the composition and function of the intestinal microbiota. Modulation of the microbiota by antibiotics also alters bile acid and glucose metabolism in mice. Hence, we hypothesized that short term administration of oral antibiotics in humans would affect fecal microbiota composition and subsequently bile acid and glucose metabolism. In this single blinded randomized controlled trial, 20 male obese subjects with metabolic syndrome were randomized to 7days of amoxicillin 500mg t.i.d. or 7days of vancomycin 500mg t.i.d. At baseline and after 1week of therapy, fecal microbiota composition (Human Intestinal Tract Chip phylogenetic microarray), fecal and plasma bile acid concentrations as well as insulin sensitivity (hyperinsulinemic euglycemic clamp using [6,6-2H2]-glucose tracer) were measured. Vancomycin reduced fecal microbial diversity with a decrease of gram-positive bacteria (mainly Firmicutes) and a compensatory increase in gram-negative bacteria (mainly Proteobacteria). Concomitantly, vancomycin decreased fecal secondary bile acids with a simultaneous postprandial increase in primary bile acids in plasma (p<0.05). Moreover, changes in fecal bile acid concentrations were predominantly associated with altered Firmicutes. Finally, administration of vancomycin decreased peripheral insulin sensitivity (p<0.05). Amoxicillin did not affect any of these parameters. Oral administration of vancomycin significantly impacts host physiology by decreasing intestinal microbiota diversity, bile acid dehydroxylation and peripheral insulin sensitivity in subjects with metabolic syndrome. These data show that intestinal microbiota, particularly of the Firmicutes phylum contributes to bile acid and glucose metabolism in humans. This trial is registered at the Dutch Trial Register (NTR2566).